Westonci.ca offers quick and accurate answers to your questions. Join our community and get the insights you need today. Get detailed and precise answers to your questions from a dedicated community of experts on our Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Sure, let’s solve the equation [tex]\( x^2 - 2x = 9 \)[/tex] by completing the square.
1. Start with the given equation:
[tex]\[ x^2 - 2x = 9 \][/tex]
2. Move the constant term to the other side to set up a standard quadratic form:
[tex]\[ x^2 - 2x - 9 = 0 \][/tex]
3. To complete the square, we first need to consider the quadratic expression [tex]\( x^2 - 2x \)[/tex].
4. Take the coefficient of [tex]\( x \)[/tex], divide by 2, and square it:
The coefficient of [tex]\( x \)[/tex] is [tex]\(-2\)[/tex].
[tex]\[ \left(\frac{-2}{2}\right)^2 = 1 \][/tex]
5. Add and subtract this square term inside the equation to maintain equality:
[tex]\[ x^2 - 2x = 9 \][/tex]
[tex]\[ x^2 - 2x + 1 - 1 = 9 \][/tex]
6. Rewrite the left side as a perfect square and simplify the equation:
[tex]\[ (x - 1)^2 - 1 = 9 \][/tex]
[tex]\[ (x - 1)^2 - 10 = 0 \][/tex]
7. Move the constant term [tex]\(-10\)[/tex] to the other side of the equation:
[tex]\[ (x - 1)^2 = 10 \][/tex]
8. Take the square root of both sides to solve for [tex]\( x \)[/tex]:
[tex]\[ x - 1 = \pm \sqrt{10} \][/tex]
9. Solve for [tex]\( x \)[/tex] by isolating it:
[tex]\[ x - 1 = \sqrt{10} \quad \text{or} \quad x - 1 = -\sqrt{10} \][/tex]
[tex]\[ x = 1 + \sqrt{10} \quad \text{or} \quad x = 1 - \sqrt{10} \][/tex]
10. So, the solutions are:
[tex]\[ x = 1 + \sqrt{10} \approx 4.162 \][/tex]
[tex]\[ x = 1 - \sqrt{10} \approx -2.162 \][/tex]
These are the solutions to the equation [tex]\( x^2 - 2x = 9 \)[/tex].
1. Start with the given equation:
[tex]\[ x^2 - 2x = 9 \][/tex]
2. Move the constant term to the other side to set up a standard quadratic form:
[tex]\[ x^2 - 2x - 9 = 0 \][/tex]
3. To complete the square, we first need to consider the quadratic expression [tex]\( x^2 - 2x \)[/tex].
4. Take the coefficient of [tex]\( x \)[/tex], divide by 2, and square it:
The coefficient of [tex]\( x \)[/tex] is [tex]\(-2\)[/tex].
[tex]\[ \left(\frac{-2}{2}\right)^2 = 1 \][/tex]
5. Add and subtract this square term inside the equation to maintain equality:
[tex]\[ x^2 - 2x = 9 \][/tex]
[tex]\[ x^2 - 2x + 1 - 1 = 9 \][/tex]
6. Rewrite the left side as a perfect square and simplify the equation:
[tex]\[ (x - 1)^2 - 1 = 9 \][/tex]
[tex]\[ (x - 1)^2 - 10 = 0 \][/tex]
7. Move the constant term [tex]\(-10\)[/tex] to the other side of the equation:
[tex]\[ (x - 1)^2 = 10 \][/tex]
8. Take the square root of both sides to solve for [tex]\( x \)[/tex]:
[tex]\[ x - 1 = \pm \sqrt{10} \][/tex]
9. Solve for [tex]\( x \)[/tex] by isolating it:
[tex]\[ x - 1 = \sqrt{10} \quad \text{or} \quad x - 1 = -\sqrt{10} \][/tex]
[tex]\[ x = 1 + \sqrt{10} \quad \text{or} \quad x = 1 - \sqrt{10} \][/tex]
10. So, the solutions are:
[tex]\[ x = 1 + \sqrt{10} \approx 4.162 \][/tex]
[tex]\[ x = 1 - \sqrt{10} \approx -2.162 \][/tex]
These are the solutions to the equation [tex]\( x^2 - 2x = 9 \)[/tex].
We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.